Pharmacokinetics of meropenem in critically ill patients receiving continuous venovenous haemofiltration: A randomized controlled trial of continuous infusion versus intermittent bolus administration - Jamal, Janattul-Ain; Mat Nor, Mohd Basri; Mohamad Nor, Fariz Safhan; Udy, Andrew A; Wallis, Steven C; Lipman, Jeffrey; Roberts, Jason A. (Elsevier, 2015)
The objective of this study was to describe the pharmacokinetics of meropenem, administered by continuous infusion (CI) or intermittent bolus (IB), in critically ill patients receiving continuous venovenous haemofiltration (CVVH) and to evaluate the frequency of pharmacokinetic/pharmacodynamic target attainment with each dosing strategy. This was a prospective, randomised controlled trial in critically ill patients receiving CVVH and administered meropenem by CI or IB. Serial meropenem concentrations in plasma and ultrafiltrate were measured after administration of a standard total daily dose (4 g/day on Day 1, followed by 3 g/day thereafter) on two occasions during antibiotic therapy. Meropenem pharmacokinetic parameters were calculated using a non-compartmental approach. Sixteen critically ill patients receiving CVVH concurrently treated with meropenem were randomised to CI (n=8) orIB dosing (n= 8). IB administration resulted in higher maximum concentrations (Cmax) [64.7 (58.9–80.3)and 64.8 (48.5–81.8) mg/L, respectively] on both sampling occasions compared with CI (P< 0.01 and P= 0.04, respectively). CI resulted in a higher meropenem steady-state concentration (Css) on occasion 1 [26.0 (24.5–41.6) mg/L] compared with the minimum concentration (Cmin) observed for IB patients [17.0(15.7–19.8) mg/L;P< 0.01]. CVVH contributed to ca. 50% of meropenem total clearance in these patients. The administered meropenem doses resulted in plasma drug concentrations that were >4×the targeted susceptibility breakpoint (2 mg/L) for 100% of the dosing interval, for both groups, on both occasions. CI could be an alternative to IB for meropenem administration in critically ill patients receiving CVVH.